If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 120 = x Solving 120 = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 120 + -1x = x + -1x Combine like terms: x + -1x = 0 120 + -1x = 0 Add '-120' to each side of the equation. 120 + -120 + -1x = 0 + -120 Combine like terms: 120 + -120 = 0 0 + -1x = 0 + -120 -1x = 0 + -120 Combine like terms: 0 + -120 = -120 -1x = -120 Divide each side by '-1'. x = 120 Simplifying x = 120
| 121=-8m+7(1-7m) | | -10-1=7x-5-x | | -18.04-4.9v+1.6v=14.7v+4(-18.1v+19.97) | | X(a+3)+y(a+3)=0 | | -3(8-11j)=-5(12-6j) | | -3=3x-6x+18 | | 4y-8x=10 | | 55x-11y=253 | | -3(8-11j)=-5(12-j) | | -5d+19-4d=-6(4d+19)-4d | | 8x-15-4x=13 | | 15x+(15)=6 | | 5(-6n+3)=165 | | -4(-18+6n)=-6(13n+15) | | 3x-7=14+2 | | 4x-4-x=-4 | | 11-3s=8 | | 1(-7x+1)=-55 | | 5(-6+3)=165 | | y=3sinx+-4 | | 15.6t-2(9.3t+15.2)=3.7t+2.9t+4.16 | | 7x-3-6x=3 | | (3y-28)/7=y/3 | | 15.6t-2(9.3t+15.2)=3.7t+2.9t+4.16t | | 15.6t-2(9.3t+15.2)=3.7t+2.9t+4.6t | | 7x+(10)=3 | | (x-28)/7=y/3 | | -5(5x+3)=45 | | 30(c+4)=900 | | 21=x-87+2x | | -19.82+18.5b=-9(-3b-12.72) | | X+0.16X=9600 |